Accuracy of INA-CBGs Claim Documentation and Its Association with Reimbursement Delays in Hospitals: A Systematic Review - Sulaiman Rasid; Ekorini Listiowati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Timely reimbursement of health insurance claims is essential for hospital financial sustainability and health system efficiency. However, reimbursement delays remain common, particularly in case-based payment systems, and are frequently linked to inaccuracies in claim documentation and supporting records. Despite increasing research on claim management, evidence remains fragmented and lacks a comprehensive synthesis of how documentation accuracy influences reimbursement timelines. This systematic review aims to synthesize empirical evidence on the accuracy of hospital insurance claim documentation and examine its association with reimbursement delays, focusing on key determinants and managerial implications. A systematic literature review was conducted following PRISMA 2020 guidelines. Peer-reviewed studies published between January 2019 and March 2025 were searched in Scopus, PubMed, Web of Science, and Google Scholar using predefined MeSH terms and Boolean operators. The initial search identified 1,245 records. After removing 314 duplicates, 931 articles underwent title and abstract screening, resulting in 253 full-text articles assessed for eligibility. Of these, 187 were excluded due to methodological or topical limitations. Ultimately, 10 studies met all inclusion criteria and were included in the qualitative synthesis. Five major determinants of documentation accuracy were identified: administrative completeness, clinical documentation and coding accuracy, information system integration, organizational governance, and human resource capacity. Inaccurate documentation was consistently associated with higher rates of pending claims, repeated verification cycles, and prolonged reimbursement timelines. Hospitals implementing standardized procedures, internal audits, and continuous training demonstrated improved claim timeliness. Documentation accuracy functions as a critical mediating factor influencing reimbursement performance. Strengthening governance, workforce competency, and system integration is essential to reduce claim delays in case-based payment environments.